1996
DOI: 10.1021/ja9541138
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Syntheses of Bisporphyrins, Bischlorins, and Biscorroles, and of Porphyrin−Chlorin and Porphyrin−Corrole Heterodimers

Abstract: The stepwise syntheses and characterization of a series of symmetrical and unsymmetrical bisporphyrins, bischlorins, and biscorroles, and of porphyrin−chlorin and porphyrin−corrole dyads possessing ethylene, phenyl, and stilbene linking units are described. The methodology for synthesis of 10-substituted corroles 2 and their cobalt complexes 9 via a,c-biladiene salts 1 was first developed, and then extended to provide biscorroles (e.g., 4 and 5) linked through the 10-positions with phenyl linker units. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 62 publications
1
49
0
Order By: Relevance
“…In the last few years we have been interested in the synthesis and characterization of dyads where two different tetrapyrrolic macrocycles are covalently linked [15][16][17][18]. Porphyrin dimers have been extensively used as models of photosynthetic systems and have afforded useful information on the factors influencing elementary photosynthetic processes [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years we have been interested in the synthesis and characterization of dyads where two different tetrapyrrolic macrocycles are covalently linked [15][16][17][18]. Porphyrin dimers have been extensively used as models of photosynthetic systems and have afforded useful information on the factors influencing elementary photosynthetic processes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As part of these studies we have reported our results on the synthesis and characterization of 1-[5-(10,15,20-triphenylporphyrinyl)]-3-[10-(2,18-diethyl-3,7,8,12,13,17-hexamethylporphyrinyl)] benzene (TPP-DEHMP) dyads [17], and we demonstrated that whereas electronic communications are negligible, as evidenced by electrochemical studies of these compounds, there exists a unidirectional energy transfer process between the TPP and DEHMP subunits. Recently we have also reported the synthesis of some symmetrical and unsymmetrical dyads of corrole [15]; because of the peculiar electronic properties of corrole, studies of these compounds can be particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…121 A dimeric structure consisting of a chlorin e 6 derivative with an appended etioporphyrin unit was reported as well. 122 Rhodochlorin XV dimethyl ester 44 presents an interesting case as two different crystal forms were found. 123 They form different crystal packing arrangements and overall both show only small deviations from Δ24.…”
Section: Phytochlorins and Related Compoundsmentioning
confidence: 99%
“…The crude compound was subjected to silica gel column chromatography using petroleum ether/CH 2 7, 110.2, 114.0, 128.4, 128.5, 134.3, 134.7, 135.2, 135.9, 136.1, 136.3, 138.1, 138.4, 145.8, 148.3, 148.7, 156.8, 157.1, 157.3 C 72.67, H 4.31, N 4.13; found C 72.75, H 4.25, N 4.26. Bromo-10,15,20-tri(p-tolyl)-21,23-dithiaporphyrin (15): Compound 15 was prepared under similar reaction conditions as described above for 14 by treating 10,15,20-tri(p-tolyl)-21,23-dithiaporphyrin (19, 55.0 mg, 0.0901 mmol) in CHCl 3 (15 mL) at room temperature with NBS (16.0 mg, 0.0901 mmol) at room temperature for 10 min.…”
Section: -Bromo-101520-tri(p-tolyl)-21-oxa-23-thiaporphyrin (14)mentioning
confidence: 99%
“…Asymmetrical porphyrin dyads containing different macrocycles such as porphyrin-phthalocyanine, [1] porphyrin-chlorin, [2] porphyrin-corrole [3] and porphyrin-heteroporphyrin [4] have receiving attention recently, because the singlet-state energy levels of two macrocycles in these types of dyads are arranged favorably for efficient transfer of energy in the metal-free state. Earlier reports on covalently linked porphyrin dyads were mainly limited to systems containing two of the same type of macrocycles such as two normal porphyrins (N 4 core).…”
Section: Introductionmentioning
confidence: 99%